2021
DOI: 10.3389/fmolb.2021.780284
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Deleterious Mutations on Structure, Function and Stability of Serum/Glucocorticoid Regulated Kinase 1: A Gene to Diseases Correlation

Abstract: Serum and glucocorticoid-regulated kinase 1 (SGK1) is a Ser/Thr protein kinase involved in regulating cell survival, growth, proliferation, and migration. Its elevated expression and dysfunction are reported in breast, prostate, hepatocellular, lung adenoma, and renal carcinomas. We have analyzed the SGK1 mutations to explore their impact at the sequence and structure level by utilizing state-of-the-art computational approaches. Several pathogenic and destabilizing mutations were identified based on their impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…HOPE server suggests that V2074I and V2148A might disrupt the protein function as they are located near highly conserved region, whereas I2134T/A and Q2696H/R may not interfere protein function, as the mutant residues are more acceptable at these positions than the wild residue. In addition, researchers have studied the effect of point mutations on the stability of protein aided molecular dynamic simulation study [ 51 , 52 ]. It has been reported that I591D point mutation in alpha-dystroglycan caused instability of protein [ 51 ], whilst another study has reported less RMSD deviation in mutant models than wild model of serum and glucocorticoid-regulated kinase 1 (SGK1) protein [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOPE server suggests that V2074I and V2148A might disrupt the protein function as they are located near highly conserved region, whereas I2134T/A and Q2696H/R may not interfere protein function, as the mutant residues are more acceptable at these positions than the wild residue. In addition, researchers have studied the effect of point mutations on the stability of protein aided molecular dynamic simulation study [ 51 , 52 ]. It has been reported that I591D point mutation in alpha-dystroglycan caused instability of protein [ 51 ], whilst another study has reported less RMSD deviation in mutant models than wild model of serum and glucocorticoid-regulated kinase 1 (SGK1) protein [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers have studied the effect of point mutations on the stability of protein aided molecular dynamic simulation study [ 51 , 52 ]. It has been reported that I591D point mutation in alpha-dystroglycan caused instability of protein [ 51 ], whilst another study has reported less RMSD deviation in mutant models than wild model of serum and glucocorticoid-regulated kinase 1 (SGK1) protein [ 52 ]. Zhang et al observed less deviation in wild type of human cytochrome P450 A2 protein than mutant F186L mutant model [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation in multiple kinases is the most general pathway that leads to tumors' development. [96][97][98][99][100][101] Mutated kinases are constitutively active and thus cause various cellular irregularities, leading to cancer initiation or growth. Mutation in signaling pathways leads to several diseases, including cancer and AD.…”
Section: Mark4 Mutationsmentioning
confidence: 99%
“…Mutation in multiple kinases is the most general pathway that leads to tumors’ development 96–101 . Mutated kinases are constitutively active and thus cause various cellular irregularities, leading to cancer initiation or growth.…”
Section: Introductionmentioning
confidence: 99%
“…PARK7 acts as both a causative and carcinogenic gene and plays a crucial role in oxidative stress [10]. Because mutations in PARK7 cause various complex diseases, we studied several variants of PARK7 using state-of-the-art computational approaches [12][13][14][15][16]. We took 152 mutations of the whole protein to explore their consequences in disease progression.…”
Section: Introductionmentioning
confidence: 99%